1997
DOI: 10.1099/00221287-143-5-1631
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of sexual reproduction in Phytophthora cactorum by phospholipids is not due to sterol contamination

Abstract: Phytophthora cadorum did not form oospores on basal medium unless phosphatidylcholine (lecithin) or phosphatidylethanolamine (cephalin) was added. After removal of putative sterols by aminopropyl column chromatography, the activities of lecithin and cephalin were increased 47-and 2*8-fold, respectively, thus confirming the previous reports that sterols are not essential for sexual reproduction in this organism. Thin-layer chromatography (TLC) of the commercial lecithin revealed the presence of an unknown inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…But a lack of sterol supply never affects the fungal growth of P. cactorum [M. Ponchet et al, unpublished data]. Stimulation of reproduction organ formation could be obtained by bringing phospholipids to P. cactorum [154,155] or to Pythium aphanidermatum [156], even with synthetic compounds [M. Ponchet et al, unpublished data]. This later result excludes that the biological activity of phospholipids results from their contamination by sterols, in contrast to previous conclusions [157].…”
Section: Sterols In Oomycete Physiologymentioning
confidence: 64%
“…But a lack of sterol supply never affects the fungal growth of P. cactorum [M. Ponchet et al, unpublished data]. Stimulation of reproduction organ formation could be obtained by bringing phospholipids to P. cactorum [154,155] or to Pythium aphanidermatum [156], even with synthetic compounds [M. Ponchet et al, unpublished data]. This later result excludes that the biological activity of phospholipids results from their contamination by sterols, in contrast to previous conclusions [157].…”
Section: Sterols In Oomycete Physiologymentioning
confidence: 64%
“…Results from previous Phytophthora studies showed the stimulatory effect of lipids on the production of oospores. In Phytophthora cactorum , basal medium supplemented with phosphatidylcholine (PtdCho) enhanced oospore formation (Ko, ; Jee et al ., 1997; 2002). To examine the effect of PtdCho on sexual development of PsGK5 ‐silenced transformants, T2, T8, WT and CK were grown on Plich's medium containing 0, 2 or 4 mg ml −1 PtdCho respectively.…”
Section: Resultsmentioning
confidence: 99%
“…plemented with phosphatidylcholine (PtdCho) enhanced oospore formation (Ko, 1988;Jee et al, 1997;. To examine the effect of PtdCho on sexual development of PsGK5-silenced transformants, T2, T8, WT and CK were grown on Plich's medium containing 0, 2 or 4 mg ml -1 PtdCho respectively.…”
Section: Psgk5 Is Essential For Oospore Productionmentioning
confidence: 99%
“…Additionally, the accumulated sterol functions to regulate the life cycle of P. cactorum (Nes & Stafford, 1983 ). However, it was subsequently found that sterols are stimulatory but not essential to sexual reproduction in P. cactorum (Jee et al, 1997 ; Ko, 1985 ; Ko & Ho, 1983 ). Sexual oospores can overwinter and survive in the soil for years, even without host presence.…”
Section: Life Cyclementioning
confidence: 99%